Traditional and cyberbullying co‐occurrence and its relationship to psychiatric symptoms. Issue 1 (3rd October 2016) - Tural Hesapcioglu, Selma; Ercan, Filiz
Abstract: Background: The effect of cyberbullying accompanied by traditional bullying on mental health has been less studied. In this study, the frequency, co‐occurrence, and the relationship to psychiatric symptoms of traditional bullying and cyberbullying among bullies and victims are examined. Methods: All of the high schools in the province of Mus, Turkey were stratified according to Placement Test for High Schools admission points for 2014–2015. By choosing schools using simple random sampling, 1276 students were reached. Students were given the Brief Symptom Inventory and three separate scale assessments: peer bullying rating, cybervictimization, and cyberbullying scales. Results: High scores in all subscale scores of bullying and victimization were significantly related to higher depression, anxiety, low self‐esteem, somatization, and hostility scores. For people who were exposed to cyberbullying in addition to traditional bullying, the severity of the psychiatric symptoms was significantly higher. For all psychiatric symptoms, major predictors were gender, total victimization score, and total cybervictimization score. Moreover, the bullying total score was among the predictors of low self‐esteem and hostility. Conclusion: Cybervictimization and cyberbullying occur less often than traditional bullying and victimization, but people who were exposed to or performed cyberbullying were also exposed to or performed traditional bullying. The addition of cyberbullying to traditional bullying is associated with more intense psychiatric symptoms.